(untitled) (Security Dialogues, 2025)
Liberal democracy as a current and dominant political model in the world represents a kind of equilibrium of a multitude of social relations and connections between the people who make up the society. Democracy as a form of political arrangement has freedom and equality in its essence.In order to enable or realize these two main postulates, society creates a system based on norms and institutions, which in turn model the citizenship of man today. Part of the institutions of the system are the security institutions, whose main mission is the guarantor of one of the basic human motives, security. The security services, like no other institution, in the realization of their mission use means and methods whose possible abuse devastates the entire political system and society in general. This is the foundation of the need for adequate control that will ensure their legal operation. Legality in the operation of the security services is imperative because their work methodology encroaches on the most basic human rights, they have information whose misuse is a flagrant violation of human freedom and rights. A fact that is established in the history of mankind. The world, the region and our country are witnessing the abuse of these institutions, which created great consequences for the future. Macedonia has witnessed several abuses of these institutions since independence until now. The last abuse that was discovered in 2015, with the illegal wiretapping, is the largest so far in terms of its scope and substance. From it, materials were illegally created for a large part of the political and media public, the business community, the judiciary, the prosecutor’s office as well as other segments of society. Even today, the dilemma about the integrity of the persons and the institutions managed by them, for which there is material from the illegal wiretapping, is still relevant. It is legitimate to question whether we can call ourselves a free society if a large part of the elite daily performs important duties aware that someone owns a part of their privacy. Therefore, it is quite natural that the quality of the control of the security services rises to the rank of an indicator of the degree of democracy in a society. Macedonia has entered the fourth decade of liberal democratic life, from a legal and normative point of view it is creating a model of parliamentary and civil control of services, but the practice is disappointing, confronting us with the fact that the form has no substance, that the declarative differs from the real.